Geometry, absorption and luminescence of small Ar clusters. (3rd May 2022) - Dhiman, Mukul; Douady, Julie; Gervais, Benoit
Abstract : We investigate the lowest excitonic levels of small argon clusters, Ar N = 1 − 13, by means of the Hole-Particle Pseudopotential (HPP) formalism introduced by Dupláa and Spiegelmann. This formalism allows us to model the excited states associated to Rydberg orbitals with higher accuracy than previous studies based on the Diatomics-In-Molecule (DIM) approach, as used by Naumkin and Wales. In contrast to the DIM method, the HPP formalism predicts the excitation to localise mostly on two atoms rather than three, for the relaxed geometry of the lowest triplet state. The hole localisation on a dimer is associated to the appearance of a large electric dipole, which depends on the isomer geometry. This dipole indicates the strong Pauli repulsion experienced by the Rydberg electron, which pushes it out of the cluster. For clusters at their ground state equilibrium geometry, we observe the formation of a singlet-state band associated with the 4 s Ar orbital, well separated from the upper states, which matches quite well with the so-called surface exciton band observed experimentally. GRAPHICAL ABSTRACT: UF0001